Direct visualization of microwires in hybrid depth electrodes using high‐resolution photon‐counting CT - Steven Smeijers; Walter Coudyzer; Elina Keirse; Vasiliki Bougou; Thomas Decramer; Tom Theys (Epilepsia Open)
Abstract Hybrid depth electrodes are increasingly being used for epilepsy monitoring and human neurophysiology research. Microwires extending from the tip of the Behnke‐Fried (BF) electrode into (sub)cortical areas allow to isolate single neurons and perform microstimulation. Conventional CT or MRI visualize the entire microwire bundle as an artifact extending from the BF electrode tip with low resolution, without proper identification of individual microwires. We illustrate the first direct visualization method of individual microwires using high‐resolution photon‐counting CT (PCCT). Coregistration of the PCCT scan with a preoperative MRI can visualize individual wires directly in cortex, which is an advantage as it provides feedback on the accuracy of the implantation method and can guide future implantations. This PCCT technique allows for accurately depicting individual microwires which could be relevant for neuroscientific research through improved visualization and implantation of specific cortical and subcortical brain areas. Plain Language Summary Researchers are using hybrid depth electrodes to study epilepsy and brain activity. These electrodes, called Behnke‐Fried (BF) electrodes, have microwires at the tip that can record single neurons and stimulate brain areas. Regular CT or MRI scans do not show the individual microwires clearly. The authors use a new high‐resolution photon‐counting CT (PCCT) technique, which can show each individual microwire in the brain. By combining PCCT with MRI, the authors can precisely see where the microwires are located. This could improve future implantation surgeries and brain research.